Memahami Kecemasan Mahasiswa di Solo Raya: Kontribusi Kepribadian, Dukungan Sosial, dan Gender - Sulistyani, Maritza Nurila; Hertinjung, Wisnu Sri (Universitas Al Azhar Indonesia, 2024)
Students often face new challenges during lectures, such as academic pressure that can affect the psychological conditions of students, especially anxiety. Personality factors and social support have a role in influencing anxiety. This study examines the relationship between personality and social support with anxiety in undergraduate students in Solo Raya, and to determine differences in anxiety based on gender. This study uses a Quantitative Correlational Approach involving 360 active students aged 18-25 from state and private universities in Solo Raya. The research instrument includes an anxiety scale, personality and social support. Sampling uses a simple random sampling technique. Data analysis is carried out by multiple linear regression analysis and product-moment correlation. The results showed that there was a significant relationship between personality and social support with anxiety (F = 290.270; p = 0.000; p = 0.05). There is a significant negative relationship between personality and anxiety (r = -0.781; p = 0.000) and between social support and anxiety (r = -0.132; p = 0.012). This study found that women experience anxiety of 3.075 higher than men. The effective contribution of personality variables and social support for anxiety is 61.9%. Practical benefits are contributing to developing counseling programs and more effective psychological support in the tertiary environment.Keywords – Anxiety, College Student, Personality, Social Support.